Local Wisdom of Batik Kudus: Integration of Ethnoscience Learning in Islamic Elementary Schools - Ahsani, Eva Luthfi Fakhru; Rusilowati, Ani; Indriyanti, Dyah Rini; Widiyatmoko, Arif (Universitas Negeri Semarang, 2024)
Students' lack of understanding of local wisdom is a significant problem in elementary schools. Especially in Kudus, batik art which contains cultural and scientific values ​​has not been utilized optimally in learning at school. This research aims to describe integrated ethnoscience learning with the local wisdom of Batik Kudus for elementary school students. This type of research is field research. Meanwhile, this research approach is a qualitative approach with descriptive methods. The location of this research is MI NU Miftahul Ulum Kudus. Data collection techniques are interviews, observation and documentation. The data analysis techniques used are data display, data reduction, and conclusion drawing. The results of this research are that the use of local wisdom of Batik Kudus in ethnoscience learning can be a learning approach that can activate students. Integration of Local Wisdom of Batik Kudus in Ethnoscience Learning for Grade B Elementary School Phase B students in learning using ecoprint activities. This activity provides students with skills in studying local culture, especially related to batik Kudus, which will be integrated into learning. The integration of local wisdom of Batik Kudus in learning is able to develop critical and creative thinking skills and foster a sense of love and pride in local culture.